The Compliant Joint Toolbox for MATLAB: An Introduction With Examples - Malzahn, Joern; Roozing, Wesley; Tsagarakis, Nikos (IEEE robotics & automation magazine, 2019)
This article presents the Complianhis Compliant Joint Toolbox for the modeling, simu lation, and controller development of compliant robot actuators. The object-oriented toolbox is written in MATLAB/Simulink. In a few lines of code, it can batch-generate ready-to-use joint actuator model classes from multiple parameter sets, in corporating a variety of nonlinear dynamics effects.